Réponses

2014-05-15T22:46:12+02:00
Bonsoir,

1) j(x)=ax+b\\\\\left\{\begin{matrix}j(-3)=7\\j(8)=-15 \end{matrix}\right.\ \ \ \ \ \ \ \ \ \left\{\begin{matrix}a\times(-3)+b=7\\a\times8+b=-15 \end{matrix}\right.\ \ \ \ \ \ \ \ \ \left\{\begin{matrix}-3a+b=7\\8a+b=-15 \end{matrix}\right.

soustrayons la première équation de la deuxième : 

(8a + b) - (-3a + b) = -15 - 7
8a + b + 3a - b = -22
11a = -22
a = -22/11
a = -2

Remplaçons a par -2 dans l'équation -3a + b = 7.

-3 * (-2) + b = 7
6 + b = 7
b = 7 - 6
b = 1

Par conséquent : 
\boxed{j(x)=-2x+1}

2) j(5)=-2\times5+1\\\\\boxed{j(5)=-9}